Kontekstualisasi Islam Tradisional dalam Bingkai Filsafat Perennial; Studi Wacana Pluralitas dan Masa Depan Agama - Husna M. Amin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Religion is a fundamental need for human being and cannot be changed by other forms, such economic is politic, culture, science etc. Religion is a symbol for giving the mean of live comprehensively. Relegion concepyually is considered an ultimate non material cocial fact. The man cannot feel any usefulnese of Religion without understanding basics corectly, rationally, the contemporary moslem schoolars studied the problem realted to religion seriously. The writing try to refocus the same thing. However, it wiil be concentrated an the vision and comprehensive understanding about iraditional Islam in Perennial Phylosophy approach. Iraditional Islam is relevan offer for solusing the problem of harmony and dialogical approach.